INCLUSIÓN DEL TERCERO CIVIL RESPONSABLE Y DEBIDO PROCESO JUDICATURA PENAL DE LIMA NORTE AÑO 2018-2019 - Moreno Brito, Humberto Gregório (2020)
Present in our punitive procedural reality a problem that harms one of the procedural subjects such as the responsible third party, it is the moment of their incorporation into the process, because each judiciary makes a different interpretation of article 111 of the Criminal Procedure Code , it is specified that this must be before the culmination of the stage of the preparatory investigation, at the beginning of the preparatory investigation, identified the active subject of the crime, raising questions, because there is a violation of fundamental rights especially respecting the right to defense , therefore, the problem of our investigation is what are the inclusion criteria of the civil third party responsible for the protection of due process, from the perspective of the criminal judiciary of ICA 2019 ?. The objective of our investigation follows from this problem: Determine what are the inclusion criteria of the civil third party responsible for the protection of due process, from the perspective of the ICA criminal judiciary. 2019. Our research studies an issue that is the subject of discussion in doctrine and jurisprudence and that the controversy remains without making substantive changes through a legislative amendment, a plenary agreement or other legislative measure that leads to correcting the people who are judged. Without having committed a crime. Our proposal in the methodological field, has a quantitative approach considering the doctrine and criminal and constitutional procedural jurisprudence around the subject. As well as the reading of the connoisseurs of the problem through the application of the survey such as lawyers and operators of the criminal judiciary. x Keyword. Fundamental rights, Due process, defense right, Third civil responsible, accusatory guarantee.